SPECTRUM OF BIOCHEMICAL ALTERATIONS IN PATIENTS WITH COVID-19 - Ali, Humaira; Nadeem, Ali; Alam, Junaid Mahmood; Naureen, Shazia (Pakistan Journal of Physiology, 2021)
Background: The COVID-19 pandemic has claimed millions of lives around the globe. In addition to respiratory involvement, multi organ failure has also been noted in these patients. We tried to assess the biochemical abnormalities in these patients to have a better understanding of this disease and its complications. Methods: Adult patients (n=107) who tested positive for COVID-19 by RT-PCR were included in this study. Blood was analysed for Urea, Creatinine, Ferritin, Lactate Dehydrogenase (LDH), Calcium, Magnesium and Phosphorus in Cobas C501 (Roche Diagnostics) using spectrophotometric technology. Sodium, Chloride, Potassium and Bicarbonate were analysed on NOVA electrolyte analyser using ion-selective electrodes. Results: Urea and creatinine were elevated in 33.6% and 22.4% patients respectively. Ferritin and LDH were high in 88.8% and 93.5% patients respectively. Reduced levels of electrolytes was observed , i.e., Sodium in 44.9%, Potassium in 22.4%, Bicarbonate in 53.3%, Calcium in 48.6%, and Phosphorus in 23.4% patients. There were no significant differences in abnormalities in the different age groups (p>0.05). Conclusion: COVID-19 patients suffer from pulmonary disease as well as multi-organ involvement as seen by the biochemical alterations, and this should be kept in mind while treating these patients. Pak J Physiol 2021;17(2):24–6